Russia-India cooperation on Post-American Afghanistan - Ivan Safranchuk; Alexandre Knyazev (Vestnik MGIMO-Universiteta)
Russian foreign policy has long championed multipolarity in international relations. As relations between Russia and the West have deteriorated, Russia has sought to establish a Eurasian project involving non-Western great powers. India has been identified by Russia as one of the major pillars of this global realignment. However, India’s global reach and power have been undermined by its entanglement in regional disputes and volatile relations with some of its partners. While some minor differences exist on the regional level in Eurasia between Russia and India, a major disagreement has been the role of the Shanghai Cooperation Organization, which Russia views as a global organization, and India sees it as regional. Our analysis suggests that the US military presence in Afghanistan, along with its plans for geoeconomic and geopolitical dominance in Eurasia, has been a major distracting factor in Russia-India relations. The US withdrawal from Afghanistan and the decline of its influence may provide new opportunities for regional cooperation between Russia and India. Our research indicates that Afghanistan may be one such country where the interests of Russia and India can converge. Both countries are interested in a stable and secure Afghanistan, and both may be willing to accept Taliban rule, subject to certain conditions, if it helps achieve that goal. In Central Asia, Russia and India have previously pursued divergent agendas, with Russia being somewhat protective of its natural sphere of interests. However, we conclude that with the elimination of external disturbances in the form of US military occupation of Afghanistan, the interests of both countries could be reconciled in relation to Central Asia. By working in synergy, Russia and India could collaborate more effectively in this region.